Quasiconformal Harmonic Mappings Related to Janowski Alpha-Spirallike Functions - Aydoğan, Melike; POLATOĞLU, YAŞAR (Amer Inst Physics, 2 Huntington Quadrangle, Ste 1No1, Melville, Ny 11747-4501 Usa, 2014)
Let f = h(z) + g(z) be a univalent sense-preserving harmonic mapping of the open unit disc D = {z/vertical bar z vertical bar < 1}. If f satisfies the condition vertical bar omega(z)vertical bar = vertical bar g'(z)/h'(z)vertical bar < k, 0 < k < 1 the f is called k-quasiconformal harmonic mapping in D. In the present paper we will give some properties of the class of k-quasiconformal mappings related to Janowski alpha-spirallike functions.
Keywords: k-quasiconformal mapping; Distortion theorem; Growth theorem; Coefficient inequality